Stability of antenna support belts - Yu. V. Krasnoshchekov; M. Y. Zapoleva (Вестник СибАДИ)
Introduction. The article deals with the issues of stability of compressed belts of lattice construction, as systems in the form of continuous rods consisting of panel elements. Currently, the estimated length of compressed elements is established by design standards for calculating stability without taking into account variability due to the influence of numerous random and systemic factors. This approach does not encourage the improvement of design solutions, the quality of their execution and the control of the structure. And most importantly, it does not allow to realize the reserves of the bearing capacity of structures laid down by the norms. The purpose of this study is to identify and substantiate the reserves of the bearing capacity of antenna supports of a lattice structure according to the criterion of stability of compressed belts.Materials and methods. It is shown that the values of the calculated length coefficient are set by norms with a margin, due, in particular, to ensuring the reliability of structural systems of compressible elements. It is proposed to consider the estimated length of compressed elements as a random variable. The problem of probabilistic estimation of the free (calculated) length of a centrally compressed element as a parameter of the critical force of loss of stability is solved. The possible normative and calculated values of the calculated length coefficient are given, ensuring the reliability of the calculation of compressed antenna support belts, adopted in the current design standards. To assess the variability of stability indicators, the task is to conduct experimental studies, in particular, with the measurement of vibration frequencies of full-scale structures. By controlling the variability indicators of the calculated length coefficient, it is possible to regulate not only reliability, but also the load-bearing capacity reserves provided for by design standards.Conclusions. The proposed approach to the calculation of stability allows to control the calculated values of the calculated length coefficient by controlling statistical variability (coefficient of variation). If there are available methods for measuring indicators, the approach described in the article to calculating compressed elements for stability can be an effective means and tool for improving design solutions, the quality of their execution and control of the structure.